Dietary adjustments: a dilemma faced by both Buddhist monastics with diabetes and the clinicians managing them - S. B. Adikari; S. P. Wickramage; N. S. Kalupahana; D. M. U. R. K. Pussepitiya; C. N. Antonypillai (Sri Lanka Journal of Medicine, 2020)
No abstract available